2020
DOI: 10.3390/rs12060947
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Spatial Distribution of Swordfish (Xiphias gladius) Using Fishery and Remote Sensing Data: Approach and Resolution

Abstract: Swordfish, Xiphias gladius (Linnaeus, 1758), is a commercially important species that is widely distributed throughout three oceans. This species inhabits oceanic waters with preferred environmental ranges and migrates vertically to the surface layer for feeding. However, the spatial distribution pattern and habitat preferences of swordfish have been rarely studied in the Pacific Ocean due to the wide geographic range of this species. This study examined the spatial distribution and preferred ranges of environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The CENPO has been referred to as a zone of high swordfish abundance (Hinton & Deriso, 1998;Su et al, 2020) and the observation that swordfish reproduction occurs year-round in the equatorial Pacific Ocean (Nishikawa et al, 1985;Palko et al, 1981) indicates that the CENPO nursery has the potential to be a large contributor of swordfish recruits to the NPO. This is of particular interest for future stock assessments and management as the Hawaiian fishery provides some 38% of the domestic catch of swordfish (Ito & Childers, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The CENPO has been referred to as a zone of high swordfish abundance (Hinton & Deriso, 1998;Su et al, 2020) and the observation that swordfish reproduction occurs year-round in the equatorial Pacific Ocean (Nishikawa et al, 1985;Palko et al, 1981) indicates that the CENPO nursery has the potential to be a large contributor of swordfish recruits to the NPO. This is of particular interest for future stock assessments and management as the Hawaiian fishery provides some 38% of the domestic catch of swordfish (Ito & Childers, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of previous studies on the environmental preferences of swordfish, surface environmental variables, including temperature, salinity, dissolved oxygen, net primary productivity, northward and eastward sea water velocity, and the two‐dimensional variable mixed layer depth, were selected as candidates for describing the surface habitat of swordfish in the Western Indian Ocean (Brodie et al, 2018; Chang et al, 2012; Evans et al, 2014; Scales et al, 2017; Su et al, 2020). For the subsurface environment, water temperature, salinity, net primary production, and dissolved oxygen were selected as critical variables to be gradually added to the model at 100 m intervals to a maximum depth of 500 m. All marine environmental data were downloaded from the COPERNICUS website (http://marine.copernicus.eu/) using monthly averaged data from 2017 to 2019 and coupled with species occurrence data.…”
Section: Methodsmentioning
confidence: 99%
“…3.1.6. Swordfish (Xiphias gladius) Swordfish (Xiphias gladius) has the widest distribution of all billfishes [73,74] and can be found in all three oceans [75] throughout temperate, subtropical and tropical regions, [76] mainly between 45 • N and 45 • S [73,74]. A study by Evans et al (2014) [77] suggested that most of the individuals tagged spent the vast majority of their lifetime within the 15 and 45 • S latitudinal range.…”
Section: Pacific Bluefin Tuna (Thunnus Orientalis)mentioning
confidence: 99%
“…There is a broad and quasi-continuous maturation-spawning region associated with the warm waters of the central-western intertropical band [83]. However, information is lacking about this species' spatial structure, spawning grounds, habitat preferences and population composition [75,77,84]. [72].…”
Section: Pacific Bluefin Tuna (Thunnus Orientalis)mentioning
confidence: 99%